Kala-azar Burden in Bangladesh- An Overview (Community Based Medical Journal, 2021)
Kala-azar is one of the major public health problems in Bangladesh and the disease is endemic for many decades. In SEA Region, VL is reported from 109 contiguous districts bordering Bangladesh, India and Nepal. Approx. 147 million people at risk in these three countries with an estimated 50,000 new cases each year. Kala-azar or Leishmaniasis is a disease caused by protozoan parasites of the Leishmania genus. It is transmitted by the sand fly named Phlebotomus argentipes and affects largely the socially marginalized and the poorest communities. The parasite migrates to the internal organs such as liver, spleen and bone marrow and if left untreated, will almost always result in the death of the host. Signs and symptoms include fever, weight loss, fatigue, anemia, and substantial swelling of the spleen and occasionally liver. In Bangladesh, kala-azar cases were reported from 45 of 64 districts, >90% of cases were reported from just 10 districts. Mymensingh accounted for more than 50% of the total kala-azar cases reported in Bangladesh. Research in recent years has demonstrated the utility of non-invasive diagnostic modalities such as the direct agglutination test and rapid tests based on the immune response to the rK39 antigen. Primary kala-azar now can be easily recognized and effective treatment is available. Clinical trials in Bangladesh have reported encouraging results with amphotericin B (recommended as a third-line drug by the National Malaria Eradication Programme). Until a safe and effective vaccine is developed, a combination of sandfly control, detection and treatment of patients and prevention of drug resistance is the best approach for controlling kala-azar.CBMJ 2020 January: Vol. 09 No. 01 P: 43-50